Circulating miRNA-195-5p and -451a in Patients with Acute Hemorrhagic Stroke in Emergency Department - Mauro Giordano; Maria Consiglia Trotta; Tiziana Ciarambino; Michele D’Amico; Federico Schettini; Angela Di Sisto; Valentina D’Auria; Antonio Voza; Lorenzo Salvatore Malatino; Gianni Biolo; Filippo Mearelli; Francesco Franceschi; et al. (Life, 2022)
(1) Background: In our previous study, acute ischemic stroke (AIS) patients showed increased levels of circulating miRNAs (-195-5p and -451a) involved in vascular endothelial growth factor A (VEGF-A) regulation. Here, we evaluated, for the first time, both circulating miRNAs in acute intracerebral hemorrhagic (ICH) patients. (2) Methods: Circulating miRNAs and serum VEGF-A were assessed by real-time PCR and ELISA in 20 acute ICH, 21 AIS patients, and 21 controls. These were evaluated at hospital admission (T0) and after 96 h (T96) from admission. (3) Results: At T0, circulating miRNAs were five-times up-regulated in AIS patients, tending to decrease at T96. By contrast, in the acute ICH group, circulating miRNAs were significantly increased at both T0 and T96. Moreover, a significant decrease was observed in serum VEGF-A levels at T0 in AIS patients, tending to increase at T96. Conversely, in acute ICH patients, the levels of VEGF-A were significantly decreased at both T0 and T96. (4) Conclusions: The absence of a reduction in circulating miRNAs (195-5p and -451a), reported in acute ICH subjects after 96 h from hospital admission, together with the absence of increment of serum VEGF-A, may represent useful biomarkers indicating the severe brain damage status that characterizes acute ICH patients.